KONDISI RUANGAN KERJA PADA TIGA PABRIK KAYU LAPIS DI SUMATRA SELATAN - Maman Mansyur Idris; Sona Suhartana (Jurnal Penelitian Hasil Hutan, 1988)
An investigation   on   working   conditions   of  three  plywood  factories  in  South   Sumatra   was conducted in 1987; The  objective is to find  out  the  workers judgement   about   their  working  conditions in  terms  of  conveniences.The   total  of  265   respondents   from  plywood  factories employed  in  the  processing  steps  of  wood  preparation, peeling,  reeling, unreeling, veneer  drying, veneer  preparation,   gluing,  pressing, finishing, quality  control, packaging, workshops and laboratories were interviewed.The  results showed that  in  each processing  step, more  than  60%  respondents  felt their  working space conditions were  far  from being convenient   due  to  inappropriate   air circulation, dust, bad  smell noise, and  vibration.